Brother Bear [videorecording (DVD)] - Blaise, Aaron; Walker, Bob; Phoenix, Joaquin; Moranis, Rick (Disney DVD : Distributed by Buena Vista Home Entertainment, 2004)
A young Native American boy's father is killed by a mother bear protecting her cubs. With revenge on his mind, Kenoia sets out into the woods only to find himself magically transformed into the creature he hates most, a bear. Luckily, a bear cub befriends him and Kenoia sets out to become human again. Kenoia begins to see the world through the eyes of what was once his prey and is forced to learn a lesson about nature and life. In the meantime, Kenoia's brother hunts him on his own mission of revenge and honor.